Assistance With School Library Revitalization To Improve The Reading Literacy Movement Among Students Of SDN 1 Tempuran, Ponorogo - yogi banar sasongko; Huril A'ini; Riza Ashari; Hartomi Maulana; Hudan Ngisa Anshori (Shof Journal of Social Impact, 2024)
This service focuses on revitalizing the school library to increase the reading literacy movement among students at SDN 1 Tempuran, Ponorogo. The progress of a nation's civilization is not simply measured by abundant natural resources and the amount of human resources, but rather the quality of human resources. To improve this quality, in the 21st century Indonesia needs to develop literacy skills. Reading or literacy activities require effective facilities and infrastructure, one of which is the library. Libraries are closely related to reading, reading culture, and interest in reading. However, in reality, the SDN 1 Tempuran library is still not neatly organized and has not been used effectively and efficiently. The aim of this service is to carry out the library revitalization process and increase students' interest in reading. Data collection methods were collected through interviews, observation and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Service is carried out in three stages, namely planning, implementation and reporting. The results of this service: 1) Library revitalization, carried out by redecorating the library, classifying books, making library visit books, making library manuals and creating a library website for SDN 1 Tempuran. After the revitalization stage was completed, several central activities were carried out in the library, such as socialization of the new administration system, competitions to determine reading ambassadors, poetry and speeches. The library functions as an alternative place for learning. Thus, it can be concluded that library revitalization can increase students' reading interest and the library functions as it should.